Isothermal Amplification of Nucleic Acids: The Race for the Next “Gold Standard” - Oliveira, Beatriz B.; Veigas, Bruno; Baptista, Pedro Viana (Frontiers in Sensors, 2021)
Nucleic acid amplification technologies (NAATs) have become fundamental tools in molecular diagnostics, due to their ability to detect small amounts of target molecules. Since its development, Polymerase Chain Reaction (PCR) has been the most exploited method, being stablished as the “gold standard” technique for DNA amplification. However, the requirement for different working temperatures leads to the need of a thermocycler machine or complex thermal apparatus, which have been preventing its application in novel integrated devices for single workflow and high throughput analysis. Conversely, isothermal amplification methods have been gaining attention, especially for point-of-care diagnosis and applications. These non-PCR based methods have been developed by mimicking the in vivo amplification mechanisms, while performing the amplification with high sensitivity, selectivity and allowing for high-throughput analysis. These favorable capabilities have pushed forward the implementation and commercialization of several platforms that exploit isothermal amplification methods, mostly against virus, bacteria and other pathogens in water, food, environmental and clinical samples. Nevertheless, the future of isothermal amplification methods is still dependent on achieving technical maturity and broader commercialization of enzymes and reagents.